PENGARUH CITRA PERUSAHAAN DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DI SAN PRIMA SEJATI - Fakhrunniza, Muhammad (Smart Education, 2025)
Abstract:Creating maximum customer satisfaction is one way to retain customers so that companies can survive in the face of competition. The purpose of this study is to test the influence of corporate image and service quality on customer satisfaction. This study uses a quantitative approach through the distribution of questionnaires. The technique used in sampling is using the census technique and the Likert scale as a measuring tool. Data collection was carried out by distributing questionnaires to 100 Pharmacy respondents who had subscribed to PT. San Prima Sejati for at least one year and were located in Medan City. Data were analyzed using statistical testing using SPSS version 26.0. Data analysis techniques used quantitative analysis, including validation and reliability test analysis, correlation coefficient test, simple and multiple regression analysis, determination coefficient test, t test and f test. The results of the study showed. From the results of the analysis it was concluded that corporate image and service quality had a significant effect on customer satisfaction. Keyword:Corporate Image; Service Quality; Customer Satisfaction Abstrak: Menciptakankepuasanpelanggansecaramaksimalmerupakan salah satucaradalammempertahankanpelanggansehinggaperusahaandapatbertahandalammenghadapipersaingan. Tujuan penelitianiniuntukmengujiadanyapengaruhcitraperusahaan dan kualitaspelayananterhadapkepuasankonsumen. Penelitianinimenggunakanpendekatankuantitatifmelaluipenyebarankuesioner. Teknik yang digunakandalampengambilansampeladalahmenggunakantekniksensus dan skala Likert sebagaialatukurnya. Pengumpulan data dilakukandenganpenyebarankuesionerkepada100respondenApotekyang sudahberlangganan pada PT. San Prima Sejati minimal satutahun dan berwilayah di Kota Medan. Data dianalisismenggunakanpengujianstatistikmenggunakan SPSS versi 26.0.Teknik analisis data menggunakananalisiskuantitatif, meliputianalisis uji validasi dan reliabilitas, uji koefisienkorelasi, analisisregresisederhana dan berganda, uji koefisiendeterminasi, uji t dan uji f. Hasil penelitianmenunjukkan.Darihasilanalisisdisimpulkanbahwa citraperusahaan dan kualitaslayananberpengaruhsecarasignifikanterhadapkepuasanpelanggan. Kata kunci: Citra Perusahaan;KualitasLayanan;KepuasanPelanggan